Differences between mid‐urethral sling outcomes in diabetic and nondiabetic women. Issue 2 (3rd January 2020) - Chung, Doreen E.; Antosh, Danielle D.; Umpierrez, Denise; Barbosa, Zonia; Yurteri‐Kaplan, Ladin; Grimes, Cara L.
Abstract: Aims: The aim is to assess whether subjects with diabetes mellitus (DM) have greater urinary retention and increased post‐void residual volume (PVR) following mid‐urethral sling (MUS) surgery. Methods: This multi‐center retrospective study included patients who underwent MUS (2012‐2016). Baseline data included demographics, comorbidities, urinary symptoms, urodynamics data, PVR, and responses to validated questionnaires (UDI6 and IIQ7). Intraoperative data, postoperative voiding trial results, postop questionnaires, and complications were also noted. Patients with and without DM were compared. Significance was defined as P  < .05. Results: A total of 605 MUS were included, 538(89%) without DM and 67(11%) with DM, of which 69% were transobturator and 31% retropubic. No differences were seen in urinary retention and passing void trial(79% DM vs 81% non‐DM; P  = .72). Mean PVR at discharge was similar between groups (136 mL DM vs 139 mL non‐DM; P  = .922). There were no differences between groups in UDI6 and IIQ7 sum scores at baseline and 1 month. DM subjects reported more bother at baseline on certain UDI‐6 and IIQ‐7 items including frequent urination, leakage related to urgency, and feeling frustrated. At 3 months postop, all subjects demonstrated improvement in scores. Interestingly, patients with DM reported worse quality of life on the IIQ7 sum. Conclusions: Among subjects with well‐controlled diabetes and more comorbidities who underwent MUS there were few differences in postoperative voiding dysfunction or PVR compared to nondiabetic women. DM patients were more bothered at baseline by urge‐related symptoms. Quality of life following sling surgery appears to be worse in patients with DM at 3 months based on IIQ7. This data suggests that diabetic women with lower HbA1C can be counseled similarly to these complication rates and voiding dysfunction after MUS.